Effects of judo training on bones - Ciaccioni, S.; Condello, G.; Guidotti, F.; and Capranica, L. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to provide a systematic literature review on the osteogenic effects of judo (PROSPERO: CRD42016041803). The online search was conducted according to the inclusion criteria: observational studies and clinical/interventional trials in English from inception to June 2016; bone health, bone mineral density (BMD), diameters, impact force, and bone turnover marker (BTM) outcomes. Thirty-four studies were included and graded for their methodological quality ("fair" quality: 79.4%). The most used assessment method (44.1%) was X-ray absorptiometry. A positive association between judo and bone health/status emerged. Findings support site-specific BMD accrual in children, adolescents, adult athletes, and in premenopausal and postmenopausal female practitioners. Bone turnover markers revealed a hypermetabolic status in high-level judo athletes. The osteogenic stimuli of judo seem to protect athletes from alterations in bone metabolic balance due to weight loss cycling. Sexual dimorphism was found between judoka in bone diameters and mass, and significant differences in bone breadths emerged between elite and nonelite judokas. The fall techniques reduced bone impact force and velocity with respect to "natural" fall. Further longitudinal, cross-sectional, and interventional researches are required. This article provides useful information on bone for health sport scientists, coaches, and practitioners, stimulating future research lines on judo. In particular, coaches and physical trainers should consider introducing judo fall techniques in their training plans to prevent fall-related injuries, especially relevant in the older population. Conversely, coaches are urged to carefully control weight cycling dietary habits of their athletes, which can produce serious metabolic responses on bones.The purpose of this systematic review was to determine which type of swim-specific training is most beneficial to enhance swimming performance and to determine which specific strength- or power-related tests better predict swimming performance. A search was conducted on PubMed, Cochrane Plus, and SPORTDiscus up to June 2018. Studies were distributed into 2 main categories: swim-specific dry land resistance training (SDLRT) and specific in- water swimming power training (SSWPT). From 1,844 citations, 25 met the inclusion criteria. It was determined that SSWPT was the most appropriate method to improve swimming performance, with tethered swimming protocols being the most studied and effective. In addition, SDLRT was a competent method to enhance swimming performance, and specifically, the inclusion of inertial training might evoke greater improvements in both strength/power capacities and swimming performance, than traditional resistance training. In conclusion, tether forces showed the greatest associations with swimming performance, although the efficacy of tethered swimming as an SSWPT method is yet to be confirmed. Further research should focus on the effects of SDLRT to verify the greater transfer of dry land resistance practices to swimming performance, with inertial training being potentially more beneficial than traditional resistance training.